Workability, Strength, Modulus of Elasticity, and Permeability Feature of Wheat Straw Ash-Incorporated Hydraulic Cement Concrete - Katman H.Y.B. (MDPI, 2023)
The extensive use of Portland cement (PC) in the manufacturing of concrete is responsible for the depletion of natural resources that are part of cement production. Cement supply is permanently threatened by the ongoing depletion of natural materials, including sand, limestone, and clay. Concurrently, the incineration of agricultural residues presents a significant ecological problem. This study explores the substitution of cement in concrete with 5%, 10%, 15%, and 20% wheat straw ash as an environmentally friendly alternative. The purpose of this investigation is to evaluate the effect of substituting wheat straw ash (WSA) for PC on the mechanical characteristics of concrete. A total of 75 concrete samples were made by cement or cement + WSA/fine aggregate/coarse aggregate ratio of 1:1, 5:3, and water-to-cement ratio was kept constant at 0.50. All of these specimens were cured and tested at 28 days. The properties tested in the paper were workability, compressive strength, splitting tensile strength, flexural strength, modulus of elasticity, and permeability. The outcomes showed that the substitution of PC with WSA 10% resulted in the greatest concrete strength. In contrast, the mechanical properties and permeability of concrete were reduced when 20% WSA was substituted for PC at 28 days. In addition, the slump value dropped as increasing the content of WSA diminished the weight of PC in the concrete. This could be attributed to the fact that the water content in the WSA 20% concrete was not enough for mechanical strength. Other concretes with WSA showed similar properties to those of the WSA 10% concrete. It was concluded from the results that since the WSA 10% concrete showed the best properties, it can be recommended as the best recipe in this research work. 2022 by the authors.